Formulation And Effectiveness Test of Tansdermal Patch of Ethanol Extract of Ginger (Zingiber officinale Rosc. Var Amarum) As Antiemetic - Arini Syarifah; Shintia L. Charisma; Nabila Nabila; Inas Kanina (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Shogaol and gingerol, compounds in ginger, can act as antiemetic. Ginger extract was formulatedby patch transdermal to increase the effectiveness of therapy and to minimize the side effects. Inthis study, maceration with ethanol 96% was used as extraction method and phytochemical screeningwas carried out to the extract to identfy the exctracted compounds. The formulation of transdermalpatch used matrix method with ginger extract concentrations of 0,5 gr (F1), 1 gr (F2), and 1,5 gr (F3).Evaluation of patch was carried out by organoleptic test, patch weight, thickness, tensile strength,elongation at break, modulus young, moisturizer test, and folding endurance. Effectiveness test usedwistar mice by observed the pica response and a decreasing in kaolin consumption. The yield of theextract obtained was 6,46% and it contained essential oils, flavonoids, steroids, and polyphenols. Thebest patch characteristics of the concentration was F3 with a patch weight of 0,39 gr, thickness 0,23mm, tensile strength 1,32 N/mm2, elongation at break 129,52%, young's modulus 0,96 mPa, humidity1,32%, and folding endurance >200 times. F3 was also the most effective formulation with 6%response of pica and 93,11% of decreasing in kaolin consumption observed in day 9. In conclusion, F3can reduce nausea and vomiting.